Proposed upgrading works of Cameron Highlands public district library for Perbadanan Perpustakaan Awam Pahang (PPAP) at 39000 Tanah Rata, Cameron Highlands, Pahang Darul Makmur / Norain Zulaika Abu Hassan - Abu Hassan, Norain Zulaika (Faculty of Architecture, Planning and Surveying, 2011)
The library is very important in our life and it has become almost part of our life. Library is so close to everyone either for kids,teenagers,usually of the are students,adults and veteran. So the library can give the big effect and can influence human’s life. The library known as an educational centre because it is a place used for a collection of useful material or in the othe words,library is a collection of sources,resources,and services on finding information. The library also can become as a community centre because library suitable to organized an event for community. This type of community centre more focusing at the public library. Usually public library become a place which is the community gathered in one place where an event are organized. So that’s why library is very close in human lifestyle. Because of above aspect,the design of library should be suitable for whom is come to the library. Everyone can come to the library,so the scope of design is important because the library interior must have the function of space for the visitors. The space of the library must follow the requirement of the public library which is it must be provided by all the facilities and services such as reading equipment,study equipment,audio and visual room and many more. The plan of the library is the most important element because interior designers use the plan to develop the new idea of space requirement so the space can become as well as client and visitors need. The design must suitable with the status of the library which is the biggest library of pahang and must provided with all kinds of services and the safe place because the safety aspect is important in design.